118k views
4 votes
Lim x-1 x³-2x²+3x-2/(2x^4-3x+1)

1 Answer

3 votes

Since the limit becomes the undetermined form


\displaystyle \lim_(x\to 1) (x^3-2x^2+3x-2)/(2x^4-3x+1) \to (0)/(0)

it means that both polynomials have a root at
x=1. So, we can fact both numerator and denominator:


x^3-2x^2+3x-2 = (x-1)(x^2-x+2)


2x^4-3x+1 = (x-1)(2x^3+2x^2+2x-1)

So, the fraction becomes


((x-1)(x^2-x+2))/((x-1)(2x^3+2x^2+2x-1)) = (x^2-x+2)/(2x^3+2x^2+2x-1)

Now, as x approaches 1, you have no problems anymore:


\displaystyle \lim_(x\to 1) (x^2-x+2)/(2x^3+2x^2+2x-1) \to (2)/(5)

User Vlad The Impala
by
5.3k points